Adaptive responses of large-seeded lentils across diverse Indian climates - Ashok Kumar Parihar; Kali Krishna Hazra; Amrit Lamichaney; Debjyoti Sen Gupta; Jitendra Kumar; Anil Kumar Singh; Sankar Prasad Das; Muniyandi Samuel Jeberson; Parvez Ahmad Sofi; Ajaz Ahmad Lone; Jai Dev; Ashok Kumar; et al. (Heliyon)
A comprehensive understanding of crop responses to diverse environments is essential for designing efficient breeding programs. Currently, such insights are lacking for large-seeded lentils under Indian climatic conditions. Given that, this study aimed to assess the impacts of diverse climatic conditions on phenological developments and yield of large-seeded lentils. This study also aimed to determine genotype-by-environment interaction (GEI), identify mega-environments, and determine ideal testing locations to enhance the efficiency of national breeding programs. For this, diverse sets of large-seeded lentil genotypes were tested across multiple locations spanning three agroclimatic zones of India: North Hill Zone (NHZ), North Western Plain Zone (NWPZ), and Central Zone (CZ). Substantial variability was observed in days to flowering (53–147 days), maturity duration (87–200 days), reproductive period (33–65 days), grain yield (0.77–2.18 t ha−1), and 100-seed weight (2.3–4.5 g) across locations. Environment factors were the dominant contributor to the yield variability (58 %), followed by GEI (28 %), with minimal genotypic effect (8 %). The CZ exhibited higher mean yields (1.47 t ha−1) with minimal intra-zonal variations, while NHZ had a lower mean yield (1.04 t ha−1). Low-temperature conditions, particularly lower maximum temperatures during the flowering and reproductive periods (TMAXF, TMAXRP), and low cumulative heat units were associated with reduced yields. Stepwise regression analysis identified cumulative growing degree-days during the vegetative period (GDDV) in NHZ and NWPZ, and TMAXRP in CZ, as the important yield-determining factors. Extended vegetative and maturity duration negatively impacted the grain yield, whereas a significant positive correlation was observed between the reproductive period and 100-seed weight (r = +0.347, p < 0.001). Grain yield exhibited a quadratic response to 100-seed weight, with the highest yields achieved at an optimal seed weight of 3.12 g. The GGE biplot ''Which Won Where'' analysis identified two distinct mega-environments, with Durgapura (NWPZ), Sagar (CZ), Pantnagar (NWPZ), and Gurdaspur (NWPZ) emerged as ‘ideal’ testing sites with high representativeness and discriminatory scaling. The findings underscore the significant influence of environmental factors on large-seeded lentil productivity emphasizing the need for a region-specific breeding approaches at the mega-environment scale. Additionally, the study highlights the importance of focusing on stable phenology (photo-thermo insensitivity) and seed traits for broader adaptability and yield stability.